FROM THE FIELD TO THE PALACE: THE CULTURAL PRACTICE OF DELIVERING THE FIRST HARVEST BY THE KOLIMASANG COMMUNITY TO THE KING OF ADONARA - Christiyanti Abel; Sirilus Karolus Keroponama Keban (PT. Jurnal Center Indonesia Publisher, 2025)
The delivery of the first harvest by the people of Kolimasang Village to the King of Sagu in Adonara represents a symbol of agrarian relations rich in cultural and spiritual meaning. In Lamaholot tradition, the king is not only a political–traditional leader but is also regarded as a representation of cosmic power that must be respected. In this perspective, the delivery of the first harvest becomes a kind of “rite of passage” from the profane world (the field) to the sacred world (the palace). Within Lamaholot tradition, this relationship is known as the 4A: Atadiken (Human), God, Nature, and Ancestral Spirits. The findings show that the procession of delivering the first harvest has been practiced for generations since the establishment of the Adonara Kingdom. The procession is carried out for two consecutive days, Tuesday and Wednesday, during the harvest week and month, usually March or April. On Tuesday, the ritual takes place in the fields during the first harvest, the yields of which are taken to the King of Adonara in Sagu. On Wednesday, the procession takes place in Lewo Sagu Atu Matang – Tanah Kota Dolu Wewang (the palace of the Adonara king), the site of the migration of King Arkian Kamba (the first Islamic King of Adonara). Both processions are preceded by traditional ritual prayers (Bao Lolon) addressed to God, Nature, and the Ancestral Spirits (3A). The equipment involved in the procession includes the harvest yield, tuak (palm wine) in bamboo containers, coconut-shell cups, gongs and drums, spears, machetes, and traditional clothing. In the procession, the king and his kin receive the harvest in a ceremonial welcome marked by traditional rituals, during which the king wears royal attire: the lipa sarong, a jacket, and a cap. The harvested produce is not only given to members of the royal family for consumption but also distributed to the wider community (ribu ratu). A tradition that remains preserved to this day—and considered the most essential—is the distribution of the first harvest by the king and his family to widows, the poor, orphans, and abandoned children. This symbolizes love, fairness, and equitable sharing—values that continue to be upheld today.